Experimental studies of simultaneous 351 nm and 527 nm laser beam interactions in a long scalelength plasma - Moody, J; Divol, L; Glenzer, S; MacKinnon, A; Froula, D; Gregori, G; Kruer, W; Suter, L; Williams, E; Bahrf, R; Seka, W (2004)
We describe experiments investigating the simultaneous backscattering from 351 nm (3w) and 527 nm (2w) interaction beams in a long scalelength laser-produced plasma for intensities I ≤ 1×1015 W/cm 2. Measurements show comparable scattering fractions for both color probe beams. Time resolved spectra of stimulated Raman and Brillouin scattering (SRS and SBS) indicate the detailed effects of laser intensity, smoothing and plasma parameters on the scattering amplitudes.